Autonomic imbalance and atrial ectopic activity—a pathophysiological and clinical view - Scridon, Alina (Frontiers in Physiology, 2022)
The heart is one of the most richly innervated organs and the impact of the complex cardiac autonomic network on atrial electrophysiology and arrhythmogenesis, including on atrial ectopy, is widely recognized. The aim of this review is to discuss the main mechanisms involved in atrial ectopic activity. An overview of the anatomic and physiological aspects of the cardiac autonomic nervous system is provided as well as a discussion of the main pathophysiological pathways linking autonomic imbalance and atrial ectopic activity. The most relevant data on cardiac neuromodulation strategies are emphasized. Unanswered questions and hotspots for future research are also identified.